Effect of Induced Plant Expression on Ants and Extrafloral Nectaries Number in Cotton and Castor - Nalini Thiyagarajan; Revathi Mani (Jurnal Proteksi Tanaman)
Plant response to the attack of herbivores is a usual phenomenon, but the number of extrafloral nectaries (EFNs) in response to herbivore attack is least studied and recorded. The current study was undertaken to document the response of cotton (Gossypium hirsu-tum Linnaeus) and castor (Ricinus communis Linnaeus) to herbivore and artificial induction. This field research was carried out experimentally on cotton and castor in two study models. The first study was the presence of ants on plants induced by herbivore (with herbivore, without herbivore) and the number of EFNs produced by each plant. The second study was the presence of ants on artificially induced plants (damaged leaves, undamaged leaves) and the number of EFNs produced by each plant. The results revealed that EFNs numbers in cotton and castor were increased by herbivore and artificial inductions, which also induced the number of ant recruitment events in cotton and castor. Artificial induction techniques can be utilized in pest management programs to attract and conserve plant guards, viz., biocontrol agents, including ants in the field. EFN is a cheap resource in quickly and effectively maintaining consistent population levels of biocontrol agents within the crops, even during pest-free times.